Knee wraps are detrimental to the maximal squat performance of powerlifters competing in lower weight classes - Naylor, A.; Ashkanfar, A.; Liu, X.; English, R. (Kinesiology, 2023)
The aim of the study was to evaluate the efficacy of knee wraps for competitive powerlifters. To achieve this, an analysis of powerlifting results dating back to 1964 has been conducted. From these results the one repetition max (1RM) squat was evaluated, specifically examining the influence of competitors using knee wraps versus raw (allowing only neoprene knee sleeves). Student`s t-test was used to compare the 1RM squat for male raw competitors (n=270,268) to those using wraps (n=26,576); and likewise for female raw (n=136,530) versus wraps (n=11,468). Overall, the males using wraps yielded significantly higher (p<.05) 1RM squat values (203 kg ± 46.8) than their raw counterparts (195 kg ± 45.7). The females yielded modest, but significantly higher (p<.05) 1RM squat values for raw (112 kg ± 29.3), compared to wraps (111 kg ± 29.8). The results were stratified by weight classes, and it was found that males in heavier classes (105, 120, and 120+ kg) significantly benefited (p<.05) from using knee wraps (+1.3, +4.8, and +6.9 kg respectively). For the lighter weight classes (59, 66, and 74 kg) knee wraps appeared significantly detrimental (p<.05) to the 1RM squat (-8.4, -4.4, and -3.6 kg, respectively). Only the heaviest female weight class (84 kg+) saw a significant benefit (p<.05) in the use of wraps with a net gain in 1RM squat of 4.5 kg. Again, wraps were shown to be significantly detrimental (p<.05) to the lighter weight classes (47, 52, 57, and 63 kg) with a net loss in 1RM squat (-3, -5.3, -3.6, and -3.3 kg, respectively). Considering these findings, it is suggested that only males in the heaviest three weight classes (105, 120, and 120+ kg), as well as females in the heaviest weight class (84+ kg), stand to gain any benefit from the use of knee wraps in competition.